Hubungan Keuangan Neraca Bank Sentral dan Neraca Pembayaran Internasional - Mya Hayda Kharisma; Nabila Ainuz Zahro; Adilah Alya; M kholil; Rini Puji Astuti (CV. ITTC INDONESIA, 2024)
in the era of economic globalization, the relationship between central bank balance sheets and international balance of payments has become increasingly complex and essential to understand. Changes in the international balance of payments serve as key indicators of a country's economic integration with the global economy and the sustainability of its economic interactions. Conversely, central bank balance sheets are often used to evaluate a country's monetary health and policies. This research employs a literature review method to analyze the main components of both balance sheets. The results indicate that changes in the central bank balance sheet can reflect a country's economic position as seen in the international balance of payments, and vice versa. For instance, an increase in foreign currency reserves by the central bank reflects efforts to manage the national currency exchange rate. Additionally, monetary policies such as raising benchmark interest rates can affect capital flows and foreign investments, subsequently influencing the international balance of payments. Central bank balance sheets and international balance of payments serve as crucial tools in monitoring economic conditions, formulating appropriate policies, and managing financial stability and international capital flows. The close relationship between these two balance sheets allows for better decision-making in managing global uncertainty risks and maintaining external economic balance..